An evaluation of a virtual COVID-19 ward to accelerate the supported discharge of patients from an acute hospital setting. Issue 12 (2nd December 2021) - Swift, Jim; Harris, Zoe; Woodward, Alex; O'Kelly, Noel; Barker, Chris; Ghosh, Sudip
Abstract : Background/Aims: In response to high numbers of hospital admissions as a result of COVID-19, a virtual ward was implemented to achieve accelerated discharge from hospital without compromising patient safety. This study assessed the impact of this virtual ward for patients admitted to the acute hospital setting with COVID-19. Methods: A community-based intervention using digital technology and a multi-disciplinary team of specialist clinicians to monitor patients at home was established. An analysis was carried out within the service investigating the safety, health outcomes and resource use of the first 65 patients discharged from hospital into the virtual respiratory ward. Results: Red days, where an urgent response was required, decreased from 33.8% of patients in their first 3 days at the virtual ward to 10.8% in their final 3 days ( P =0.002). Four patients were readmitted to hospital, all for clotting disorders. There was one death, which was deemed unrelated to COVID-19. Length of stay was also reduced by 40.3% ( P <0.001) and estimated overall savings were £68 052 (£1047 per patient). Conclusions: The virtual ward appeared to assist with earlier discharges, had a low rate of clinically necessary re-admissions, and seemed to reduce costs without compromising patient safety. The authors believe that this intervention could be applied across other NHS trusts facing similar capacity issues as a result of COVID-19.